2011
DOI: 10.1111/j.1439-0507.2011.02103.x
|View full text |Cite
|
Sign up to set email alerts
|

Species assignment and antifungal susceptibilities of black aspergilli recovered from otomycosis cases in Iran

Abstract: Black aspergilli are among the main causative agents of otomycosis worldwide. In this study, the species assignment of black aspergilli isolated from otomycosis cases in Iran was carried out using sequence analysis of part of the calmodulin gene. The results indicate that Aspergillus niger is not the only black Aspergillus species involved in otomycosis cases in Iran: Aspergillus awamori and Aspergillus tubingensis are also able to cause ear infections. Antifungal susceptibility tests were carried out against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
19
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 31 publications
3
19
1
Order By: Relevance
“…The intraspecific and interspecific differences in the antifungal susceptibilities of Aspergillus section Nigri from previous studies were inconsistent (7)(8)(9)(10)(11)(12)(13), primarily for the azoles and amphotericin B. Our study also observed the above differences among voriconazole, terbinafine, and amphotericin B, but all the MICs were low for both species.…”
contrasting
confidence: 53%
See 1 more Smart Citation
“…The intraspecific and interspecific differences in the antifungal susceptibilities of Aspergillus section Nigri from previous studies were inconsistent (7)(8)(9)(10)(11)(12)(13), primarily for the azoles and amphotericin B. Our study also observed the above differences among voriconazole, terbinafine, and amphotericin B, but all the MICs were low for both species.…”
contrasting
confidence: 53%
“…In recent years, sequence-based molecular methods have been used successfully for species identification in this group, particularly methods using the calmodulin gene, which can distinguish all species within section Nigri (4-6). Molecular studies indicated that several species in addition to A. niger were able to cause human infections; different regions had different species of pathogenic black Aspergillus, and A. niger and Aspergillus tubingensis were the most frequently identified pathogens in previous studies (2,(7)(8)(9)(10)(11)(12)(13)(14). Additionally, it is worth noting in a clinical context that azoles exhibited different activity against the two species and that isolates from different geographical regions exhibited remarkable differences in susceptibility to azoles and amphotericin B (1-13, 15).…”
mentioning
confidence: 97%
“…Aspergillus is the most common fungus cultured from otomycosis patients, consisting of 60%‐90% of all pathogens reported in several studies from different countries. Candida is the second most, consisting of nearly 10%‐40% . In our study, Aspergillus species were isolated in 84.3% of cases (75/89), and Candida species were found in 8.9% (8/89).…”
Section: Discussionmentioning
confidence: 47%
“…In addition, this species was also identified in various otomycosis cases both in Iran and Hungary [34], [35]. Although the name A. awamori was used taxonomically correctly by Perrone et al [15], this currently used name is misleading, as this species is rarely identified in awamori fermentation processes, where mostly A. niger and A. luchuensis could be isolated [11].…”
Section: Discussionmentioning
confidence: 99%